Building big profits in real estate : - Timmerson, Wade (J. Wiley, 2004)
ilding Big Profits in Real Estate focuses on the sound strategies that everyone needs to understand before they invest in real estate. It covers important topics, such as analyzing markets, financing your projects, purchasing rental property, managing a real estate portfolio, finding new ways to invest, and understanding wholesale markets. It also reveals some of the most overlooked opportunities in the real estate market, including Section 8 rentals, wholesaling properties, and selling houses on a rent-to-own basis.